ChemInform Abstract: Selective Reductive Coupling of Nitro Compounds with Aldehydes to Nitrones in H2 Using Carbon‐Supported and ‐Decorated Platinum Nanoparticles. Issue 8 (February 2015) - Cisneros, Larisha; Serna, Pedro; Corma, Avelino
Abstract Compared to common supported metal catalysts the Pt‐C‐catalyst shows a high selectivity for nitrone synthesis.